Original papersLong-term follow-up of patients with hypertrophic obstructive cardiomyopathy treated with percutaneous alcohol septal ablation - Małek, Łukasz A.; Chojnowska, Lidia; Kłopotowski, Mariusz; Dąbrowski, Maciej; Mączyńska, Renata; Demkow, Marcin; Witkowski, Adam; Kuśmierczyk, Beata; Piotrowicz, Ewa; Konka, Marek; Rużyłło, Witold (Advances in Interventional Cardiology/Postępy w Kardiologii Interwencyjnej, 2009)
Background and aim: Alcohol septal ablation (ASA) is a well-established method of treatment of hypertrophic obstructive cardiomyopathy (HOCM). The ASA was introduced in 1995 and long-term results have not been sufficiently stuided so far. Therefore the aim of the study was to perform a long-term assessment of ASA. Methods: Study included 57 patients who underwent ASA in the Institute of Cardiology, Warsaw, Poland between November 1997 and December 2002. Evaluation consisted of clinical status assessment, echocardiographic test and symptom limited cardiopulmonary exercise treadmill test before the procedure, after 3 months (short-term follow- -up) and after median 8 years (long-term follow-up). Results: Mean maximal pressure gradient in the left ventricular outflow tract (LVOTG) before ASA was 85 ± 27 mm Hg and mean NYHA functional class was 2.56 ± 0.71. ASA led to a reduction of LVOTG to 39 ± 29 mm Hg (p < 0.0001) and improvement of heart failure symptoms (mean NYHA class 1.23 ± 0.47, p < 0.0001) at short-term follow-up. Three patients died during first five years from ablation (5.4%). There were two extracardiac deaths and one sudden cardiac death (SCD). In two other patients 2 equivalents of SCD (one appropriate cardioverter-defibrillator discharge and one resuscitated cardiac arrest) have been disclosed. All cardiac events occured in patients with LVOTG ł 50 mm Hg after ASA. Long-term follow-up revealed continuous decrease of LVOTG (p < 0.0001) and increase of percent predicted peak VO2 consumption (p < 0.03) despite deterioration of mean NYHA class (p = 0.0001) in comparison to short-term follow-up. Conclusions: Alcohol septal ablation is an effective method of LVOTG reduction which progresses in time. Despite worsening of subjectively assessed heart failure class over time, objective assessment of exercise capacity shows continuous improvement. Persistent LVOTG ł 50 mm Hg after ASA may increase the risk of sudden cardiac death.